Why Did God Make Me this Way? Anger at God in the Context of Personal Transgressions - Grubbs, Joshua B. (Journal of psychology and theology, 2014)
The present study focused on evaluating how anger at God may be related to the experience of personal moral transgression. People might view God as partly responsible for their transgressions if they attributed these transgressions to stable personal character traits that could be traced back to the way that they believe they were created by God. Viewing God as responsible for a trait that led to a transgression could lead the individual to feel angry at God. This hypothesis was tested in two studies across three samples. Results from the first study, a scenario-based experiment, supported our hypothesis. When individuals attributed a transgression to a core aspect of self, greater experiences of divine struggle were a likely result. Results from two cross-sectional samples (undergraduates and an adult web sample) revealed similar patterns regarding real-life transgression. Specifically, to the extent that people saw their personal transgressions as resulting from stable character traits, they reported greater anger toward God. This relationship was mediated by the extent to which individuals made negative interpretations of divine intent. In sum, people may experience struggles with the divine in response to their own personal transgressions, particularly when they attribute their transgressions to dispositional aspects of the self.